Hsp90 regulates the function of argonaute 2 and its recruitment to stress granules and P-bodies. - Pare, J.M.; Tahbaz, N.; López-Orozco, J.; LaPointe, P.; Lasko, P.; Hobman, T.C. (Molecular Biology of the Cell, 2009)
Argonaute proteins are effectors of RNA interference that function in the context of cytoplasmic ribonucleoprotein complexes to regulate gene expression. Processing bodies (PBs) and stress granules (SGs) are the two main types of ribonucleoprotein complexes with which Argonautes are associated. Targeting of Argonautes to these structures seems to be regulated by different factors. In the present study, we show that heat-shock protein (Hsp) 90 activity is required for efficient targeting of hAgo2 to PBs and SGs. Furthermore, pharmacological inhibition of Hsp90 was associated with reduced microRNA- and short interfering RNA-dependent gene silencing. Neither Dicer nor its cofactor TAR RNA binding protein (TRBP) associates with PBs or SGs, but interestingly, protein activator of the double-stranded RNA-activated protein kinase (PACT), another Dicer cofactor, is recruited to SGs. Formation of PBs and recruitment of hAgo2 to SGs were not dependent upon PACT (or TRBP) expression. Together, our data suggest that Hsp90 is a critical modulator of Argonaute function. Moreover, we propose that Ago2 and PACT form a complex that functions at the level of SGs.